Color In Modern Art (Damascus University Journal for engineering sciences, 2023)
The relationship between colors and fine arts, and during long ages was a relationship of unity and integration, colors lost symbols of religious, social and metaphysical feelings, and colors were the most expressive and effective tool for the artist and his understanding of the year around him. Man found this world and was happy with his existence and began to form pictures of the surrounding world on pieces of cloth and sometimes by himself pictures of the gods he imagined on religious grounds and on the basis of myths or sacred books, and these things formed pictures of this land and the history of its inhabitants. In this way, color arose as a visual artistic language with its own rules and laws.Here the problem of the research emerges by trying to understand the development of this color visual language that has proven its presence strongly in the last century through the remarkable innovations that we see in modern art, those creations that have been studied in depth by artists and researchers, but not on the level of color, and this is what This research is trying to achieve it.
Keywords: Color; Modern Art